2019
DOI: 10.1177/0194599818823180
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Lymphedema: Treatment Response to Single and Multiple Sessions of Advanced Pneumatic Compression Therapy

Abstract: Ten head and neck cancer survivors diagnosed with head and neck lymphedema (HNL) were imaged using nearinfrared fluorescence lymphatic imaging (NIRFLI) prior to and immediately after an initial advance pneumatic compression device treatment and again after 2 weeks of daily athome use. Images assessed the impact of pneumatic compression therapy on lymphatic drainage. Facial composite measurement scores assessed reduction/increase in external swelling, and survey results were obtained. After a single pneumatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…In an advanced head and neck LE patient, NIRF-LI showed newly formed functional lymphatic vessels across fibrotic surgical scar lines enabling successful re-direction of MLD toward those functional lymphatics (Figure 10b) [100]. It is also noteworthy that, in a prior review of NIRF-LI studies of unilateral BCRL patients, contralateral, undiagnosed arms exhibited increasing surface coverage of dermal backflow with stage and duration of diagnosed contralateral LE, even though cancer treatments were confined to the ipsilateral arm [93]. Other studies have found disrupted lymphatic flow on contralateral limbs in unilateral BCRL patients [94][95][96], suggesting unknown mechanisms that may work to progressively deteriorate lymphatics systemically after initial clinical LE diagnosis.…”
Section: Imaging Lymphatic Response To Le Treatmentmentioning
confidence: 91%
See 2 more Smart Citations
“…In an advanced head and neck LE patient, NIRF-LI showed newly formed functional lymphatic vessels across fibrotic surgical scar lines enabling successful re-direction of MLD toward those functional lymphatics (Figure 10b) [100]. It is also noteworthy that, in a prior review of NIRF-LI studies of unilateral BCRL patients, contralateral, undiagnosed arms exhibited increasing surface coverage of dermal backflow with stage and duration of diagnosed contralateral LE, even though cancer treatments were confined to the ipsilateral arm [93]. Other studies have found disrupted lymphatic flow on contralateral limbs in unilateral BCRL patients [94][95][96], suggesting unknown mechanisms that may work to progressively deteriorate lymphatics systemically after initial clinical LE diagnosis.…”
Section: Imaging Lymphatic Response To Le Treatmentmentioning
confidence: 91%
“…In a case of an HNC patient four weeks after RT, we imaged dermal backflow and poor drainage to cervical LN that, unlike in prior studies of untreated HNC patients, dissipated after two weeks of home treatment with an advanced pneumatic compression device (APCD) ( Figure 9 d). Indeed, in a pilot study to explore the early intervention by APCD therapy, the surface coverage of dermal backflow decreased over two weeks of treatment, suggesting that impaired lymphatic function was improved or recovered with treatment [ 93 ].…”
Section: Diagnostic Imaging Of Dysfunctional Lymphatics For Staginmentioning
confidence: 99%
See 1 more Smart Citation
“…Without enforcing supine positioning throughout the study, we cannot rule out that the increase in drainage to the cervical LNs over time was independent of position. Nonetheless, with the data presented herein, future studies that focus upon interventions, the influence of sleep (Xie et al, ), novel pneumatic compression (Gutierrez et al, ), or postural changes that might impact CSF outflow could be properly designed and powered to eliminate these artifacts. Furthermore, while ICG administration in the palatine tonsils appeared to provide a consistent measure of drainage to the LNs, CSF outflow, and transit times to draining LNs may be more accurately and noninvasively evaluated with NIRFLI following intrathecal administration as demonstrated in rodent models (Kwon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Whether impaired CSF drainage into the peripheral lymphatics increases ICP and mediates neuroinflammation in humans remains to be fully investigated not only in SANS, but other syndromes and chronic conditions in which impaired lymphatic/CSF drainage restricts clearance of protein and waste products. Methods to stimulate drainage in the CSF drainage pathways could include pneumatic compression devices (Gutierrez et al, ) or manual lymphatic drainage techniques. While pro‐inflammatory cytokines inhibit lymphatic function and drainage (Aldrich & Sevick‐Muraca, ; Aldrich et al, ; Scallan, Zawieja, Castorena‐Gonzalez, & Davis, ), till date there are limited studies on how to pharmacologically stimulate lymphatic drainage, particularly those draining the intracranial space.…”
Section: Discussionmentioning
confidence: 99%